Real-world effectiveness of CDK4/6i in first-line treatment of HR+/HER2− advanced/metastatic breast cancer: updated systematic review - Harbeck, Nadia; Brufsky, Adam; Rose, Chloe Grace; Korytowsky, Beata; Chen, Connie; Tantakoun, Krista; Jazexhi, Endri; Nguyen, Do Hoang Vien; Bartlett, Meaghan; Samjoo, Imtiaz A.; Pluard, Timothy (Frontiers in Oncology, 2025)
AimSince 2021, additional real-world evidence (RWE) has emerged on the effectiveness of cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) as first-line treatment of HR-positive/HER2-negative (HR+/HER2−) advanced/metastatic breast cancer (A/MBC), necessitating this updated review.MethodsMEDLINE®, Embase®, and Cochrane Databases (07/06/2019–01/09/2024), and key congresses (2020–2024) were searched. Studies reporting first-line CDK4/6i use, over 100 participants, and progression-free survival (PFS) and/or overall survival (OS) data were included.ResultsThis update included 82 unique studies, 42.7% for palbociclib, 7.3% for ribociclib, and 3.7% for abemaciclib; 46.3% assessed multiple CDK4/6i. In studies including multiple CDK4/6is, median PFS was 23.4–31.0 months for palbociclib, 19.8–44.0 for ribociclib, and 14.0–39.5 for abemaciclib. When reached, median OS was 38.0–58.0 months, 40.4–52.0 months, and 34.4 months, respectively. These real-world PFS and OS results were within the range of single-arm and CDK4/6i versus endocrine therapy (ET) studies, where CDK4/6i demonstrated greater benefits than ET alone.ConclusionFirst-line CDK4/6i RWE demonstrates significant clinical benefits in HR+/HER2− A/MBC. These data are important to guide clinical decision-making, as they include patients who are not adequately represented in clinical trials. Studies with longer follow-up are needed to assess long-term benefits of all three CDK4/6i therapies in HR+/HER2− A/MBC.